2009
DOI: 10.1242/jeb.025601
|View full text |Cite
|
Sign up to set email alerts
|

A novel tilapia prolactin receptor is functionally distinct from its paralog

Abstract: Supplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 36 publications
(39 reference statements)
5
54
0
Order By: Relevance
“…Branchial expression of prlr2 has been shown to be higher in the gill of tilapia abruptly transferred to SW than in those maintained in FW (Fiol et al 2009). HEK293 cells transfected with prlr2 exhibited greater tolerance to hyperosmotic stress when compared with empty vector controls or those transfected with prlr1 (Fiol et al 2009). Expression of branchial prlr1 decreases with transfer from FW to SW (Breves et al 2010a) and increases with transfer from SW to FW (Breves et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Branchial expression of prlr2 has been shown to be higher in the gill of tilapia abruptly transferred to SW than in those maintained in FW (Fiol et al 2009). HEK293 cells transfected with prlr2 exhibited greater tolerance to hyperosmotic stress when compared with empty vector controls or those transfected with prlr1 (Fiol et al 2009). Expression of branchial prlr1 decreases with transfer from FW to SW (Breves et al 2010a) and increases with transfer from SW to FW (Breves et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While the discovery of two distinct Prl molecules in tilapia suggested the evolution of distinct actions, no clear differences in osmoregulatory action have been demonstrated (Specker et al 1985). This issue has been recently revisited by Fiol et al (2009), who reported that Prl 177 and Prl 188 activate distinct downstream signalling pathways in transfected HEK293 cells expressing tilapia PrlRs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found non-A bases at the start of the adenylation sequence in most of the 3 0 RACE sequences (data not shown). There are two regions of the intracellular tail of the PRLR that are conserved in all species; box 1, which is 8 aa of mostly prolines and hydrophobic residues, is found in all isoforms and box 2, which is rich in both hydrophobic and acidic amino acid , Bole-Feysot et al 1998, is found in all long and intermediate isoforms, the hPRLR-SF1a (Trott et al 2003), and both carp short PRLR isoforms (GenBank Accessions DQ086117 and DQ086116), but not in long form PRLR2 from tilapia (Fiol et al 2009) or PRLR2 from Nile tilapia (Zhang et al 2010). The pPRLR-SF, like the majority of short isoforms, does contain box 1 but does not contain box 2 (Figs 1 and 2).…”
Section: Resultsmentioning
confidence: 99%